Relationship between Critical Thinking and Adherence to Religious Reference Groups in M.A. Students of Tehran’s Universities - Fatemeh Amooabdollahi; Khadijeh Safiri (Taḥqīqāt-i Farhangī-i Īrān)
Presence of Clergymen in religion, social and political life had been legitimized with Islamic theoretical base and historical necessity in Iran’s society. Surveys have shown that clergymen’s prestige has been changed (Particularly among the youth) after the Islamic Revolution. Regarding  the extension of critical approach and critical thinking in education system, the purpose of this research is to investigate the relation between students' critical thinking and adherence to clergymen. The statistical population included all MA students of state universities in Tehran . Three hundred seventy (370) students were selected through Kuokran's formula and PPS sampling. The results have shown that there is not a significant relation between critical thinking and adherence to clergymen. But adherence to clergymen is shown to have a negative relation with inquisitiveness and open-mindedness subscales. There is a positive relation between truth-seeking and adherence. Also there is a positive relation between critical thinking and going to non-clergy specialists of religion.